Communication in the context of glioblastoma treatment: A qualitative study of what matters most to patients, caregivers and health care professionals. (June 2023) - Boele, Florien W; Butler, Sean; Nicklin, Emma; Bulbeck, Helen; Pointon, Lucy; Short, Susan C; Murray, Louise
Background: Patients with glioblastoma have a poor prognosis and treatment is palliative in nature from diagnosis. It is therefore critical that the benefits and burdens of treatments are clearly discussed with patients and caregivers. Aim: To explore experiences and preferences around glioblastoma treatment communication in patients, family caregivers and healthcare professionals. Design: Qualitative design. A thematic analysis of semi-structured interviews. Setting/participants: A total of 15 adult patients with glioblastoma, 13 caregivers and 5 healthcare professionals were recruited from Leeds Teaching Hospitals NHS Trust. Results: Four themes were identified: (1) Communication practice and preferences . Risks and side-effects of anti-tumour treatments were explained clearly, with information layered and repeated. Treatment was often understood to be 'the only option'. Understanding the impact of side-effects could be enhanced, alongside information about support services. (2) What matters most . Patients/caregivers valued being well-supported by a trusted treatment team, feeling involved, having control and quality of life. Healthcare professionals similarly highlighted trust, maintaining independence and emotional support as key. (3) Decision-making . With limited treatment options, trust and control are crucial in decision-making. Patients ultimately prefer to follow healthcare professional advice but want to be involved, consider alternatives and voice what matters to them. (4) Impact of COVID-19 . During the pandemic, greater efforts to maintain good communication were necessary. Negative impacts of COVID-19 were limited, caregivers appeared most disadvantaged by pandemic-related restrictions. Conclusions: In glioblastoma treatment communication, where prognosis is poor and treatmentwill not result in cure, building trusting relationships, maintaining a sense of control and being well-informed are identified as critical.